Endocrine disruption in male mosquitofish (Gambusia holbrooki) inhabiting wetlands in Western Australia - Game, Clare; Gagnon, Marthe Monique; Webb, Diane; Lim, R. (Springer, 2006)
The use of gonopodial indices as potential indicators of endocrine disruption in the mosquitofish Gambusia holbrooki inhabiting south west Australian wetlands was investigated. A minimum of 50 mature males was collected from each of five water-bodies in the Swan Coastal Plain, Western Australia, in order to measure morphological features related to reproduction. A set of morphological measurements were used to derive the following indices: gonopodium length/standard body length, pre-anal length/standard body length, the index of elongation and the percentage of male fish with hooks on the distal end of the gonopodium. Indices of male mosquitofish collected from Jack Finney Lake, located in the Curtin University campus, suggest the presence of endocrine disrupting chemicals (EDCs) in this water-body, while those from Lake Kulinup suggest this is a site of concern. Indices of male fish from the Wagerup wetland, Lake Monger and Loch McNess indicate that fish inhabiting these wetlands are not affected by EDCs. This preliminary study suggests that EDCs may be present in a number of wetlands of the Swan Coastal Plain. Further study using EDC specific markers such as vitellogenin induction in male mosquitofish is required to confirm whether EDCs are present in these water-bodies.